Patients’ perception about polycystic ovarian syndrome (PCOS) in Sub-Himalayan region of India-A facility-based cross-sectional study - Richa Jaswal; Shailesh Tripathi; Dhananjay Singh; Nand Lal Gupta; Hoshiar Singh Chauhan; Suchpreet Kaur; Shireen Sharma; Sudip Bhattacharya (Journal of Family Medicine and Primary Care)
Background: In modern times, metabolic disorders are most common and one of them is polycystic ovarian syndrome (PCOS) in women, which causes high morbidity and complications. PCOS has largely been a neglected and less researched area; however, it is gaining importance in recent times as PCOS is increasing as well as it can be prevented to a considerable extent. Methods: A cross-sectional study was conducted to assess knowledge among females in government hospitals in Northern India. Data were collected using a pretested structured questionnaire on 300 women (completed 270), selected by proportionate sampling technique, and admitted in government hospitals. Data were analyzed by SPSS version 23. Results: The results showed that the mean age of respondents was 33.02 ± 9.039 years, the mean age at menarche was 12.33 ± 2.13 years, and the mean of gravida status was 1.82 ± 0.78 years. Only half of the respondents had good knowledge about PCOS. Conclusion: This study suggests that efforts are needed to reinforce women’s knowledge through setting-based awareness campaigns and health education in this context to enable them to identify and seek timely treatment and improve their quality of life.